Jazz w Europie Środkowo-Wschodniej w latach sześćdziesiątych w perspektywie… „Jazzu” (cz. 1: Synteza zjawiska) - Trudzik, Artur Mariusz (1973– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
The article aims to quantitatively and qualitatively examine the content of the monthly magazine Jazz (1960–1969) in the context of defining this type of music in Central and Eastern Europe and (preliminary) applications of materials about this region to the Western world. At the same time, it supplements the first study, analysing the period between 1956 and 1959; hence, it was given a comparative form, i.e. the text is divided into two main parts, which concern the reference to statistical data (along with the author’s commentary) and a description of the use of syncopated music in the countries of the Eastern Bloc: USSR, Czechoslovakia, GDR, Yugoslavia, Romania, Bulgaria, and Hungary. The research results showed that, in all cases, the degree of jazz development was either preserved or progressed during the four-year period.
p. 183-203
Summary in English and Russian.
Keywords: Polish press in the 20th and 21st centuries; journalism and music media; jazz music in the 1950s in Central and Eastern Europe; Jazz (periodical; 1956-1983); jazz - Europe, Central - history and criticism; jazz - Europe, Eastern - history and criticism; jazz - Poland - history; jazz - Poland - periodicals - history and criticism